Peran Guru Sebagai Learning Agent di Dalam Kitab Nashõih Al-'Ibãd - Gustiannor, Syahrani; Halilah, Halilah; Mubarak, Muhammad Zaki (PT. Sharia Journal and Education Center, 2025)
This study aims to examine the role of teachers as Learning Agents from the perspective of Sheikh Muhammad Nawawi al-Bantani's book, Nashōih al-‘Ibād, and its relationship to the concept of the teacher's role in the modern education system, particularly as stipulated in Law Number 14 of 2005 concerning Teachers and Lecturers. This study is motivated by the importance of teachers in shaping the character, spirituality, and intellectual qualities of students, serving not only as instructors but also as moral guides and agents of change. The method used in this study is a qualitative approach with library research, involving textual analysis of the contents of Nashōih al-‘Ibād and interpretation of the educational values ​​contained therein. Data were analyzed descriptively and interpretively using contemporary educational theory. The results of the study indicate that the role of teachers in the Nashõih al-‘Ibãd covers various aspects, including as a source of knowledge, spiritual guide, moral role model, motivator, facilitator, and life advisor. These roles are aligned with the four teacher competencies in Law No. 14 of 2005, but this book places a stronger emphasis on spiritual and moral aspects. Thus, the values ​​contained in Nashõih al-‘Ibād are relevant as a strengthening of the ethics of the teaching profession in the modern era, as well as a reminder that the duties of teachers are part of the prophetic heritage.